Printing materials for stomatological use - López Hernández, Loretta de los Milagros; Rodríguez Castillo, Daileny; Espinosa Tejeda, Nitza de las Mercedes (Revista 16 de abril, 2018)
<!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Printing materials are products that are used to copy or reproduce negatively the hard and soft tissues of the oral cavity. A review was carried out with the aim of characterizing the printing materials of stomatological use in terms of composition, properties, handling, dosage and uses. Databases Pubmed, Lilacs and Cumed were consulted for the collection of information, with 24 bibliographic references being useful. It was concluded that alginates have a varied use, zinquenolic paste is the most dimensionally stable printing material, the main property of the waxes is thermoplasticity and one of the best printing materials is silicone.